STEM integration: factors affecting effective instructional practices in teaching mathematics / Nor Syazwani Mohd Rasid ... [et al.] - Mohd Rasid, Nor Syazwani; Md Nasir, Nurul Akmal; Singh, Parmjit; Cheong, Tau Han (Universiti Teknologi MARA, 2020)
Malaysian Ministry of Education (MOE) has created initiatives in the Malaysian Education Blueprint (2013- 2025 that aim to increase teachers’ and students’ competencies in Science, Technology, Engineering and Mathematics (STEM) subjects and create learning experiences that will prepare students for the considerable array of STEM career fields. There are so many effective instructional practices suggested in integrating STEM education for teaching Mathematics. However, there are some factors that need to be concerned in producing effective instructional practices in teaching Mathematics. This study investigated the factors affecting instructional practices of mathematics since the implementation STEM education. Using a descriptive design method, a questionnaire was administered to 100 students and 50 mathematics teachers in Klang Valley. The overall mean score of all four factors (Lesson plan and implementation, Mathematical discuss and sensemaking, task implementation, and classroom culture) measured in this study is moderately high based on students’ and teachers’ perspectives. Teachers rated all factors higher than students’ rate. Both teachers and students agreed that classroom culture is the important factor. There are no significant differences in the mean score of factors among gender of students and teachers. There is significant difference in the mean score of factors among the achieving abilities among the students.